PENGEMBANGAN KOMIK DIGITAL SEBAGAI MEDIA PEMBELAJARAN AGAMA BUDDHA DI VIHARA GRHA BUDDHA MANGGALA BATAM - Pratama, Jimmy; Viona Viona; Wibowo, Tony (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
Vihara Grha Buddha Manggala is one of the places of worship for Buddhists in Batam, this monastery also held the Buddhist Sunday School. Buddhist Sunday School is a non-formal learning activity that are held every Sunday and is aimed for Buddhist children. With the sophistication of technology that had developed rapidly, it also impacted the diversity of forms and types of learning media, such as webtoon digital comic. By utilizing webtoon digital comic, Buddhist Sunday School students can understand the learning material better rather than through discussions and usual lectures. The aim of this research is to develop a more interesting learning media to maximize the learning activities. The result of this research is a webtoon digital comic that are designed and developed using ADDIE (Analyze, Design, Develop, Implement, Evaluate) model.